Empirical Evaluation of Broader Job Search Requirements for Unemployed Workers - Bas van der Klaauw; Heike Vethaak (Tinbergen Institute, 2022)
This paper analyses data from a large-scale field experiment where unemployed workers were randomly assigned to an additional caseworker meeting with the purpose to impose a broader job search strategy. We find that the meeting significantly increases job finding and is cost effective. However, caseworkers differ substantially in the rate at which they impose broader job search. We exploit this heterogeneity in caseworker stringency and the random assignment of unemployed workers to caseworkers within local offices to evaluate the broader search requirement. Our results show that imposing the broader search requirements reduces job finding. We argue that restricting the job search opportunities forces unemployed workers to search sub-optimally which negatively affects labor market outcomes.
Keywords: J22; J64; J65; J68; C93; 330; Unemployment; broader job search; caseworker stringency; caseworker meetings; field experiment